PENGEMBANGAN ALAT PERAGA DARI LIMBAH PLASTIK UNTUK MATERI GEOMETRI BIDANG DATAR JENJANG SEKOLAH DASAR [CREATING TEACHING AID FROM PLASTIC WASTE ON PLANE GEOMETRY IN ELEMENTARY SCHOOL] - Pangaribuan, Firman; Pangaribuan, Rut K (JOHME: Journal of Holistic Mathematics Education, 2021)
Plastic waste that is difficult to decompose is a serious problem in environmental pollution. Geometry is a difficult subject for students, and plastic waste can be used as teaching aids to help students learn geometry. This research is a type of development research and aims to develop teaching aids from plastic waste in learning plane geometry in fifth grade elementary school. The results showed that the teaching aids developed were valid, practical and effective. Teaching aids are called practical if they meet the interesting, gradation, independent, auto-correction, and contextual aspects. The validity of the teaching aids is obtained through aspects of suitability, completeness, convenience, and clarity. Based on the assessment of the three validators, an average score of 3.50 was obtained so that the teaching aids were categorized as valid. The practicality of teaching aids by students showed that 95% of students stated that they were interesting, graded, and independent, 74% of students stated that it was auto-correction and 91% stated that it was contextual. The effectiveness of the teaching aids can be seen from the significant difference between the average pre-test score of 46.2 and the post-test average score of 77.3. The props from the plastic waste that were developed are stored and will be used later for the same lesson in the future.BAHASA INDONESIA ABSTRACT: Limbah plastik yang sulit terurai adalah masalah yang serius dalam pencemaran lingkungan. Geometri merupakan pelajaran yang sulit bagi siswa, dan limbah plastik dapat digunakan sebagai alat peraga untuk membantu siswa dalam belajar geometri. Penelitian ini adalah jenis pengembangan dan bertujuan mengembangkan alat peraga dari limbah plastik dalam pembelajaran geometri bidang datar di kelas V SD. Hasil penelitian menunjukkan bahwa alat peraga yang dikembangkan valid, praktis dan efektif. Alat peraga disebut praktis jika memenuhi aspek menarik, bergradasi, mandiri, auto correction, dan kontekstual. Kevalidan alat peraga diperoleh melalui aspek kesesuaian, kelengkapan, kemudahan, dan kejelasan. Berdasarkan penilaian tiga validator diperoleh skor rata-rata 3,50 sehingga alat peraga dikategorikan valid. Kepraktisan alat peraga oleh siswa menunjukkan bahwa 95% siswa menyatakan menarik, bergradasi, dan mandiri, 74% siswa menyatakan auto correction dan 91% menyatakan kontekstual. Keefektifan alat peraga terlihat dari perbedaan yang signifikan antara skor rata-rata pre tes 46,2 dan skor rata-rata pos tes 77,3. Alat peraga dari limbah plastik yang dikembangkan disimpan dan akan digunakan kemudian untuk pelajaran yang sama di kemudian hari.